EGG MARKS the SPOT - Timberlake, Amy; Klassen, Jon (rows Nest, NSW : Allen & Unwin Childrens Books, 2021)
c
Primary school age.
Keywords: Badgers -- Juvenile fiction; Skunks -- Juvenile fiction; Chickens -- Juvenile fiction; Roommates -- Juvenile fiction; Friendship -- Juvenile fiction; Children's stories